Pemanfaatan Limbah Sekam Padi Kombinasi Daun Bambu Sebagai Pupuk Kalium Silika Pada Kelompok Karang Taruna - Wulandari, Fani; Naimah; Muhammad Irfan Taufan Asfar, Andi; Muhamad Iqbal Akbar Asfar, Andi; Karmila; Rahman (LPPM UNIVERSITAS LANCANG KUNING, 2023)
The high number of rice production and the wide area of rice fields in Pationgi Village with an intensity of harvesting 3 times a year makes Pationgi Village the largest rice producer in Patimpeng District. This rice husk waste is a problem where the Massedi Youth Organization Group who also works at the rice mill feel confused about how to process waste that is not used properly and greatly reduces aesthetics and pollutes the environment, where this waste is simply thrown away, burned and just piled up. So that with this service program it will help the community in the implementation of making potassium silica fertilizer through several methods starting from the counseling, training and mentoring stages to partners. The results of this program are able to increase partners' knowledge and productivity in processing rice husk waste from a combination of bamboo leaves into potassium silica fertilizer. The resulting product is packaged in small jerry cans with a size of 1 liter. This service was carried out in Pationgi Village by involving the maseddi youth group as partners. The results obtained from this community service are ways to handle rice husk and bamboo leaf waste by treating the waste as potassium silicate fertilizer.